Quercetin and Nano-Derivatives: Potential and Challenges in Cancer Therapy - Li XR; Qi L; Zhang XW; Wei C; Yu B; Pei TL (International Journal of Nanomedicine, 2025)
Xin-Ru Li,1 Lin Qi,2 Xi-Wen Zhang,3 Chao Wei,1 Bin Yu,1 Tian-Li Pei4 1College of Integrated Chinese and Western Medicine, Jining Medical University, Jining, Shandong Province, 272000, People’s Republic of China; 2Affiliated Hospital of Jining Medical University, Jining, 272000, People’s Republic of China; 3College of The Second Clinical Medical, Henan University of Traditional Chinese Medicine, Zhengzhou, Henan Province, 450003, People’s Republic of China; 4Guizhou University of Traditional Chinese Medicine, Guiyang, Guizhou Province, 550000, People’s Republic of ChinaCorrespondence: Tian-Li Pei, Email 562126112@qq.comAbstract: Quercetin, a prevalent flavonol compound, has gained attention for its multifaceted mechanisms of action against various cancers, highlighting its potential as an adjunctive therapy in cancer treatments. This review aims to systematically evaluate the structural optimization, mechanisms of action, and clinical applications of quercetin and its nano-derivatives in cancer treatment. Employing a bibliometric analysis of 6231 articles from the Web of Science Core Collection, we observed a notable increase in annual publications, particularly from the USA and China, indicating a growing interest in quercetin’s therapeutic potential. Our findings reveal that quercetin enhances the efficacy of conventional therapies by modulating critical signaling pathways, thereby increasing cancer cell sensitivity while simultaneously protecting normal tissues from therapy-induced damage. Structural modifications, including glycosylation, methylation, sulfation, and glucuronidation, alongside nanoparticle formulation, significantly improve the stability, solubility, and bioavailability of quercetin, enabling targeted drug delivery. Despite the promising preclinical outcomes, the clinical translation of quercetin remains nascent, necessitating further rigorous research to validate its safety and efficacy in human subjects. In conclusion, while quercetin exhibits substantial anticancer properties and therapeutic potential, future studies should focus on expanding sample sizes, elucidating metabolic pathways, and conducting comprehensive clinical trials to inform its application in oncology.Keywords: quercetin, nano-derivatives, cancer therapy, mechanisms of action, drug safety